Developing a generic, individualised adherence programme for chronic medication users - Herborg H; Haugbølle LS; Sørensen L; Rossing C; Dam P (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Objective: The scope of this article is to describe the background for and content of an adherence counselling programme with a specific focus on an individualised, multi-dimensional adherence model for patients with a potential adherence problem (a so-called 'individualised systems model').Methods: An intervention programme based on WHO's systems model for adherence was developed for implementation in primary health care and tested in a development project in Danish pharmacies in 2004-2005 in three pharmacies and 4 GP practices by 27 patients. Data were collected from the participants by registration forms, questionnaires, and focus groups. Since the programme was to support patients in the self-management process regarding choice and implementation of medication treatment, various strategies were used and different theoretical assumptions and choices made prior to setting up the study. These strategies include distinguishing between different types of non-adherence, a model for stages of change, self-efficacy, narratives, motivating interviewing strategies and coaching techniques. These strategic and theoretical choices are described in the article. Results: The strategies and theoretical reflections formed the platform for the creation of a counselling programme, which was tested in two forms, a basic and an extended version - provided by either a pharmaconomist or a pharmacist. The result section also describes a toolbox of instruments to enable pharmacy staff and GPs to tailor a counselling programme for patients individually called 'Safe and effective use of medicines'. Besides, the results include a description of how the WHO-model is transformed into an individualised counselling model.